The Impact of the Soviet Repatriation Campaign on the Eastern European Émigré Community in Argentina (1955-1963) - Galván, Maria Valeria (2017)
In response to a strong anticommunist campaign in the Western World in the 1950s, the USSR started a counter-propaganda campaign directly aimed at Eastern European émigrés living abroad to persuade them to return to Soviet territories. This policy was implemented through the founding of the International Committee for the Return to the Motherland, established in 1955 in East Berlin. This paper intends to explore the Argentinean case in the context of the post-Stalinist Soviet Repatriation campaign, aided by the historical analysis of local official period documents (mainly diplomatic and intelligence reports) and oral history, to argue that the characteristics of Argentine society in the 1950s and 60s were largely responsible for the success of local agents of propaganda and recruiters. Nonetheless, the process of repatriation also affected the subjectivity of the repatriates and called into question their sense national identity.